SUSTAINABLE ARTIFICIAL INTELLIGENCE TOOL STRATEGY AND CUSTOMER EXPERIENCE IN EYE WEAR RETAIL CHAIN STORES - Reddy, N. Suma; Singh, Dr. Gursimranjit (The journal of contemporary issues in business and government, 2022)
Artificial intelligence tools and processes have hugely impacted the retail industry and the satisfaction of online customers. With technology largely pervading all facets of our lives, people want meaningful experiences. Artificial intelligence has the ability to deliver positive experiences for customers that help build brand trust and customer satisfaction. Whether you are using your smartphone, laptop, or voice assistants such as Alexa or Siri, service on the internet is gaining new ground. This paper does a literature review of the various technological advances that optimize thecustomer experience to evoke esatisfaction (i.e., satisfaction while shopping online). E-satisfaction asa construct will be reviewed with its impact on customer purchase intention. The main results of the documentation were used to substantiate the conceptual framework introduced by the paper. The research revealed a variety of advanced solutions, benefits, but also risks that AI generates in retail, in different segments of the value chain, abbreviated CECoR, from improving the customer experience (Customer Experience, CE) with the help of virtual agents (chatbots, virtual assistants, etc.), tocost reductions (Cost, Co) by using smart shelves, and to increasing revenues (Revenue, R) due to product recommendations and personalized offers or discounts. The proposed conceptual framework is focused on customer profiles and includes recommendations on AI implementations in a retail company, from the perspective of CECoR drivers. The results of the research can be capitalized by practitioners and researchers in the field, who are presented with concrete examples of benefits, challenges, and risks generated by AI technologies. The CECoR framework could be a useful tool for both retail and AI specialists, providing common and clearguidelines for initiating and overseeing projects for integrating AI in a company’s informationsystems. This review will provide businesses and other researchers a frame of reference to conduct empirical studies in the area of Aland technology-enabled retail.